Etnomarketing: estrategias de negocio desde las raíces culturales - Ortiz, Nicolás (2016)
This article focuses on the changes that took place in consumer studies starting with the collectivist focus that etnomarketing offers in the digital age, the same that separates itself from a rational and individualist vision. Firstly, the main difficulties that the cerebral-rational point of view confronts are described, point of view from which it is considered that human beings differentiate themselves from the other species by their capacity to choose freely and rationally. Secondly, a sociocultural approach of consumption anthropology applied to business (etnomarketing) that evolves towards the view of the consumers as immerse in different social contexts, and that organize their comprehension of the world starting from their culture, is proposed. Finally, some considerations are made about the challenges of understanding the consumers in the age of social networks.